Pengaruh Konformitas Teman Sebaya terhadap Perilaku Merokok Mahasiswa di Kota Padang - Mutiara Qhairani; Shefriana Putri Pulungan; Annafi Fahdulla Alam; Fhadilla Afriliantika Irma; Friskha Hapsari; Aditia meisya putra; Mirzi Hayati; Shaztry Zalmy; Silvi Juwita (CV. ITTC INDONESIA, 2025)
Smoking behavior among college students is becoming an increasingly worrying public health problem, especially in Padang City. This study aims to examine how peers influence smoking habits among college students. The method used is a quantitative method with simple linear regression analysis. The research sample consisted of 59 active smoker students in Padang City, obtained through incidental sampling techniques. The instruments used consisted of a peer conformity scale and a smoking behavior scale, both of which have been tested for validity and reliability. The research findings show that peer conformity has a significant influence on college students' smoking behavior with a significance value of 0.000 (p <0.05) and an influence coefficient of 0.575. Higher levels of conformity will increase the tendency to smoke. These findings indicate that peer influence is very important in shaping smoking habits among college students. Therefore, interventions that focus on social norms and peer relationships are essential to reduce the number of young smokers on campus.